Nonavalent Human Papillomavirus Vaccination as a Treatment for Skin Warts in Immunosuppressed Adults: A Case Series - Simon Bossart; Valentina Imstepf; Robert E. Hunger; S. Morteza Seyed qqqJafari (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)